Green Nanotechnology and Biological Synthesis of Gold Nanoparticles from Various Plant Extracts and Their Biological Applications (International Journal of Food and Nutritional Sciences, 2022)
Nanotechnology is a trending area in research field for studying particles at nano scales and it is used over conventional methods and gives size dependent parcels of the functional accoutrements. The present review includes study on green technology for the synthesis of gold nanoparticles from various extracts of different plant parts. The green nanotechnology field that provides sustainability in various implementations. The nanomaterial synthesis using conventional nanotechnology involves the release of poisonous nanomaterials that creates the issue of nanotoxicity but the green nanotechnology helps in derogation of the risk and hazards due to the same [17]. The gold nanoparticles using plants extracts because of their diversity, sustainability and eco-friendly nature. It is concluded that gold nanoparticles synthesized using plants extract such as leaf, root, seed and fruit extracts have antioxidant and antimicrobial activity. Due to their SPR frequency, biocompatibility and tunable property gold nanoparticles has great application in cancer treatment, biosensor, drug delivery and enhancement of plant growth.